Discovery of Novel N-Acylhydrazone Derivatives as Potent Inhibitors of Sirtuin-1 - Lipson, Victoria V.; Yaremenko, Fedyr G.; Vakula, Volodymyr M.; Kovalenko, Svitlana V.; Kyrychenko, Alexander V.; Desenko, Sergiy M.; Borysko, Petro О.; Zozulya, Sergiy O. (SynOpen, 2024)
SIRT1 enzyme is a key family member of Silent Information Regulators (Sirtuins), which catalyze the deacetylation of proteins. Therefore, developing new SIRT1 inhibitors has potential application in treating cancer disease and age-related metabolic disorders. In this study, we synthesized a series of N-acylhydrazone (NAH) derivatives and performed high-throughput screening of their inhibitory activity against the recombinant SIRT1 protein by a luminescent assay. Using in silico screening, we identified a new NAH derivative that features both selectivity and a high binding affinity towards the active pocket of SIRT1 that are comparable to known inhibitors such as Ex527 and Sirtinol. Such high binding affinity makes the new derivatives promising alternatives to the available inhibitors and holds promise for developing better-targeted drugs against SIRT1 activity.
Keywords: Sirtuin1; organic synthesis; N-acylhydrazone; inhibitors; molecular docking